Health and safety needs of homeless people in Ibadan metropolis, oyo State, Nigeria (2018)
Homelessness or street life is becoming a serious emerging social and community safety problem in Ibadan. Notably, women and children remain an important population within this group and should be considered important data source by researchers in the continuous quest to find sustainable solutions to this problem. This study examined the health and safety needs of internally displaced persons in Ibadan, Oyo State, using the phenomenological research method. Respondents were sampled around major areas in Ibadan where these groups are found. Those willing to participate in the study were interviewed in any of the four major languages (English/pidgin, Hausa, Yoruba and Igbo). Forty-Three respondents comprising 14 women, 16 children and 13 youths were interviewed. The generated data were transcribed and analysed using thematic content analysis. Themes derived from the analysis of generated data showed that poverty and conflicts were major causes of internal displacement in the study area. Food and shelter were the most commonly cited health needs of the respondents. The safety needs among the respondents were health care, protection from sexual harassment, rape, physical and verbal abuse. It is concluded that paying special attention to this group will go a long way in reducing community health and safety issues. A fund for the care, well-being and resettlement of the internally displaced persons through public-private partnership among other policy-based recommendations were made.